DETERMINASI KEADILAN PAJAK, TAX MORALE TARIF PAJAK, DAN TEKNOLOGI SISTEM PERPAJAKAN TERHADAP TAX EVASION - Diana Fajarwati (Governance, 2023)
The purpose of this study is to find out whether there is an effect of tax rates on tax evasion, whether there is an effect of tax fairness on tax evasion, whether there is an effect of tax system technology on tax evasion and whether there is an effect of tax morale on tax evasion. This study uses a type of quantitative research using primary data in the form of a questionnaire. The sample used is individual non-employee taxpayers who are registered at KPP Pratama Cibitung. The sampling technique in this study used the Purposive Sampling method, namely sampling based on certain criteria from the required population. Based on calculations using the slovin formula, 100 respondents were obtained using multiple linear regression analysis techniques. Based on the tests that have been carried out, the results obtained state that Tax Rates have a significant positive effect on Tax Evasion, Tax Justice has a significant negative effect on Tax Evasion, Tax System Technology has a significant negative effect on Tax Evasion and Tax Morale has a significant negative effect on Tax Evasion.